Attenuation analysis of long-haul NLOS atmospheric optical scattering communication. (June 2016) - Zhang, Shihua; Wang, Jingyuan; Xu, Zhiyong; Song, Chao; Wang, Rong; Chen, Yiwang; Zhao, Jiyong; Wei, Yimei
Abstract: The attenuation characteristics of ultraviolet (UV) and infrared transmitting in the atmosphere is analyzed, when long-haul Non-Line-of-Sight (NLOS) optical scattering communication is considered. The effects of Rayleigh and Mie scattering to link performance are presented. Under given geometric configurations, a critical range R C is found. When communication range is shorter than R C, the attenuation of UV is lower than that of infrared. But the path loss of UV increases rapidly, while the path loss of infrared increases much slower. When communication range is longer than R C, the attenuation of UV is higher than that of infrared. Numerical values of R C under different geometries are analyzed. It is also indicated that, under arbitrary geometric configurations, the impact of the Rayleigh scattering to infrared scattering communication is weak, but to UV scattering, the Rayleigh scattering effect cannot be ignored. Highlights: A theoretical transmitting model for NLOS optical scattering communication. Effects to received power by Rayleigh scattering and Mie scattering is analysed. Path loss under long-haul UV and infrared scattering communication is compared. A critical range Rc is found an analysed.